Autobiographical Meaning Making Protects the Sense of Self-Continuity Past Forced Migration - Camia, Christin; Zafar, Rida (Frontiers in Psychology, 2021)
Forced migration changes people’s lives and their sense of self-continuity fundamentally. One memory-based mechanism to protect the sense of self-continuity and psychological well-being is autobiographical meaning making, enabling individuals to explain change in personality and life by connecting personal experiences and other distant parts of life to the self and its development. Aiming to replicate and extend these results, the current study investigated whether autobiographical meaning making has the potential to support the sense of self-continuity in refugees. We therefore collected life narratives from 31 refugees that were coded for autobiographical reasoning, self-event connections, and global narrative coherence. In line with prior research, results suggest that autobiographical meaning making relates to a higher sense of self-continuity and less psychological distress. Yet, if refugees experienced many continuing postdisplacement stressors in addition to their forced displacement, autobiographical meaning making was associated with higher self-discontinuity and greater psychological distress, especially with trauma-related symptoms such as memory intrusion and hyper-arousal. Altogether, results indicate that autobiographical meaning making potentially helps to compensate the effects of extreme biographical disruptions on the sense of self-continuity, as long as the stress caused by the biographical change is not overwhelming or too protracted.